Transcription factors FabR and FadR regulate both aerobic and anaerobic pathways for unsaturated fatty acid biosynthesis in Shewanella oneidensis - Luo, Qixia; Shi, Miaomiao; Ren, Yedan; Gao, Haichun (Frontiers in Microbiology, 2014)
As genes for type II fatty acid synthesis are essential to the growth of Escherichia coli, its sole (anaerobic) pathway has significant potential as a target for novel antibacterial drug, and has been extensively studied. Despite this, we still know surprisingly little about fatty acid synthesis in bacteria because this anaerobic pathway in fact is not widely distributed. In this study, we show a novel model of unsaturated fatty acid (UFA) synthesis in Shewanella, emerging human pathogens in addition to well-known metal reducers. We identify both anaerobic and aerobic UFA biosynthesis pathways in the representative species, S. oneidensis. Uniquely, the bacterium also contains two regulators FabR and FadR, whose counterparts in other bacteria control the anaerobic pathway. However, we show that in S. oneidensis these two regulators are involved in regulation of both pathways, in either direct or indirect manner. Overall, our results indicate that the UFA biosynthesis and its regulation are far more complex than previously expected, and S. oneidensis serves as a good research model for further work.